Kemitraan Sekolah dan Komite Sekolah Dalam Meningkatkan Mutu Pendidikan di SMP IT Raudhatul Jannah Cilegon - Supardi Supardi; Ahmad Qurtubi; Hasim Fatoni (Journal on Education, 2023)
In managing education in order for educational goals to be achieved, it must involve the community and stakeholders in managing education. Parents of students who are members of the community and users of educational services have a large portion to participate in improving the quality of education carried out by schools, so that there will be complementary partnerships and become an important part in improving the quality of education in education units. Therefore, the establishment of a school committee should be able to serve as a partner in the implementation of the school program program. This study aims to determine the form of partnership between the school management of SMPIT Raudhatul Jannah Cilegon and its school committee. In this study, the author used a descriptive qualitative method with data collection techniques by means of interviews, observations and documentation. The results showed that there is a partnership between the school and the school committee in the academic and non-academic fields, always coordinating in making plans for school activities in improving the quality of education as well as social society. The Committee is a partner of the school functioning to give consideration, support and supervision to school activities, and become a mediator between the school and all guardians of students, so that with functions and partnerships that are well established with the committee of SMPIT Raudhtul Jannah Cilegon can carry out various activity programs that aim to improve the quality of education so that the vision and mission of the school and the satisfaction of parents of students are achieved together